1997
DOI: 10.1029/97jd01388
|View full text |Cite
|
Sign up to set email alerts
|

Ion balance equation in the atmosphere

Abstract: Abstract. Cosmic rays are the main source of ions in the atmosphere at altitudes of 5-35 km. The flux of cosmic rays in the atmosphere depends on the site of observation and is controlled by the geomagnetic field. Except for the rare cases of solar proton events and Forbush decreases, cosmic ray flux varies slowly with changes of solar activity level. Thus there is quasi-stationary equilibrium between the ion production and recombination processes. Usually, the equation q=an 2 is used to describe this equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 16 publications
1
30
0
2
Order By: Relevance
“…Analysis of experimental data of balloon measurements of ion concentrations and galactic CR fluxes in the atmosphere from the ground level up to 30-35 km showed that the ion balance equation has a linear form q = bÁn instead of quadratic one q = aÁn 2 , where b is a linear recombination coefficient, q is an ion production rate proportional to the galactic CR flux, n is a light ion concentration, and a is an ion recombination coefficient (Ermakov et al, 1997). In the case of the quadratic equation n is proportional to q 0.5 and in the case of the linear equation n is proportional to q.…”
Section: Ionization Sourcementioning
confidence: 98%
“…Analysis of experimental data of balloon measurements of ion concentrations and galactic CR fluxes in the atmosphere from the ground level up to 30-35 km showed that the ion balance equation has a linear form q = bÁn instead of quadratic one q = aÁn 2 , where b is a linear recombination coefficient, q is an ion production rate proportional to the galactic CR flux, n is a light ion concentration, and a is an ion recombination coefficient (Ermakov et al, 1997). In the case of the quadratic equation n is proportional to q 0.5 and in the case of the linear equation n is proportional to q.…”
Section: Ionization Sourcementioning
confidence: 98%
“…Alternate measurements of the positive and negative conductivity were made by varying the polarity chose for the central electrodes' bias voltage. Modern balloon measurements of the ion concentration in the atmosphere (Rosen and Hofmann 1988;Ermakov et al 1997) have yielded a great diversity of results. Even accounting for different latitudes and solar activity levels, the ion concentrations obtained are not consistent with each other, which appears likely to be due to the varying extent of aerosol pollution.…”
Section: Air Conductivity Measurements On Manned Balloon Ascentsmentioning
confidence: 99%
“…3), using measurements performed by Neher (1967Neher ( , 1971 for the solar minimum and by Ermakov et al (1997) for the solar maximum conditions in both polar and equatorial regions. The agreement between our calculations and the actual measurements is quite good, especially taking into account that the calculations present some average values while measurements were done during short (hours) flights.…”
Section: Ionizationmentioning
confidence: 99%